Implementation of Restorative Justice as An Alternative in Resolution to Criminal Acts of Abuse Against Children: A Case Study at The Boyolali District Prosecutor's Office - Pandu Firmansyah; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2026)
Child abuse is a crime that causes long-term physical and psychological impacts. The retributive criminal justice system is considered incapable of providing substantive justice for both child victims and perpetrators. Restorative justice presents as an alternative paradigm that emphasizes the restoration of relationships and social reconciliation. This research uses an empirical legal method (sociolegal research) with a qualitative descriptive analytical approach through in-depth interviews, observations, and literature studies at the Boyolali District Attorney's Office. This study reveals the exclusive nine-stage mechanism at the Boyolali District Attorney's Office that integrates social rehabilitation programs as an integral part of the restorative process, an innovation that has not been widely studied at the district prosecutor's office level. Implementation is carried out through nine systematic stages, from receiving the SPDP to community outreach, with four main criteria that the latest Attorney General's circular flexed to a minimum of two requirements. Supporting factors include a strong legal basis, leadership commitment, the Rumah Restorative Justice (Restorative Justice House), and multi-stakeholder collaboration; the main obstacles include victim rejection and limited public understanding. Restorative justice has proven more effective in providing substantive and humane justice for children, in line with the principle of the best interests of the child mandated by the Indonesian legal system.